Race/Ethnicity and gender differences in health intentions and behaviors regarding exercise and diet for adults with type 2 diabetes: A cross-sectional analysis - Fox Kathleen M; Gavin James R; Grandy Susan (BMC, 2011)
Abstract Background Self-management is the cornerstone of diabetes control and prevention of complications; however, it is undetermined whether differences in intention to adopt healthy lifestyles and actual healthy behavior exist across race/ethnic groups. This study evaluated the differences across racial-ethnic groups in self-reported medical advice received and health intentions and behaviors among adults with type 2 diabetes mellitus. Methods A cross-sectional analysis of the 2007 SHIELD US survey ascertained self-reported health intentions and behaviors for regular exercise, diet, and weight management among Non-Hispanic Caucasian (n = 2526), Non-Hispanic African-American (n = 706), and Hispanic (n = 179) respondents with type 2 diabetes. Results A similar proportion of respondents from each race-gender group (43%-56%) reported receiving healthcare advice to increase their exercise (P = 0.32). Significantly more minorities reported an intention to follow the exercise recommendation compared with Non-Hispanic Caucasians (P = 0.03). More Non-Hispanic African-American (29%) and Hispanic (27%) men reported exercising regularly compared with other race-gender groups (P = 0.02). Significantly more Non-Hispanic Caucasian women (74%) and Hispanic women (79%) reported trying to lose weight compared with other groups (P < 0.0001). Conclusions Differences in health intentions and healthy behaviors were noted across race-gender groups. More Non-Hispanic African-American men reported an intention to follow advice on exercising and self-report of exercising regularly was also higher compared with other race-gender groups. More Hispanic men reported high physical activity levels than other groups. Despite an increased willingness to follow healthcare recommendations for diet, >50% of respondents were obese among all race-gender groups.